2020
DOI: 10.22610/imbr.v12i1(i).3033
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Role of Career Adaptability between Career Commitment and Career Motivation: An Empirical Investigation

Abstract: This study investigates the nexus between career commitment, adaptability and motivation, and the mediation role of career adaptability on the relationships between career commitment and motivation. Data were collected randomly from marketers working in the telecommunication sector in the Kurdistan region of Iraq through online questionnaires. There were 121 out of 285 forms received and analyzed using the structural equation modeling approach. The findings indicate that both career commitment and adaptability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(110 reference statements)
1
10
0
Order By: Relevance
“…The results showed that there is a significant correlation between career concern and career commitment, which was verified in the structural equation model, indicating that career concern has a positive predictive effect on career commitment. This finding is consistent with the results of other researchers [73,74]. It reveals that a high school student with a high level of career concern might hold a firm commitment to his/her career.…”
Section: Direct Effect Of Career Concern On Career Commitmentsupporting
confidence: 93%
“…The results showed that there is a significant correlation between career concern and career commitment, which was verified in the structural equation model, indicating that career concern has a positive predictive effect on career commitment. This finding is consistent with the results of other researchers [73,74]. It reveals that a high school student with a high level of career concern might hold a firm commitment to his/her career.…”
Section: Direct Effect Of Career Concern On Career Commitmentsupporting
confidence: 93%
“…After establishing expectations and objectives for themselves and their work position, students' CC steadily increases [62]. The CC at T1 did not signi cantly predict the CA at T2, inconsistent with the results [13,26], although the study showed that a higher occupational commitment appears to have considerable bene ts for occupational adjustment [26]. Nursing students often face substantial occupational stress at the beginning of their clinical job, as evidenced by barriers to nurse-patient communication, lack of professional knowledge, and unfamiliarity with the clinical environment, resulting in anxiety and frustration, and decreased enthusiasm for the job [63,64].…”
Section: Longitudinal Relationship Between Ca Andmentioning
confidence: 98%
“…In turn, employees with a high CC will be more motivated to do their job, be more adaptable to potential problems, and help their organizations succeed [23]. A previous study has identi ed CC as an important catalyst for CA [13]. High levels of CC enable individuals to cope with future changes, and as a result these individuals are more likely to be successful in their organizations' potential careers [24].…”
Section: Ca and CCmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it could allow them to acquire more information that allows them to prepare for the future. Career adaptability, on the other hand, develops in the context of possible longer-range motivation goals and behaviors ( Najib and Aljanabi, 2020 ), which could allow individuals to become more resilient rather than blindly adapting for the sake of it.…”
Section: Discussionmentioning
confidence: 99%